Utilization of digital prenatal services and management of depression and anxiety during pregnancy: A retrospective observational study - Rubin-Miller, Lily; Henrich, Natalie; Peahl, Alex; Moss, Christa; Shah, Neel; Jahnke, Hannah R. (Frontiers in Digital Health, 2023)
Introduction: We examined how utilization of Maven, a digital healthcare platform that provides virtual prenatal services, is associated with improvements in perceived management of anxiety and depression during pregnancy, and how medical knowledge and support may influence this association. Materials and Methods: In this retrospective study we used adjusted logistic regression to examine the relationship between digital platform use in pregnancy and perceived mental health management, and how perceived management of mental health is affected by user-reported improvements in medical knowledge and feeling supported by the platform. Effects were evaluated separately among users with and without a mental health condition. Demographics, medical history, and mental health management were self-reported. Results: Of 5659 users, 705 (12.5%) reported that Maven helped them manage anxiety and/or depression in the prenatal period. In adjusted models, users who read more articles, sent more messages to care advocates, or had more appointments with providers were more likely to report improved management of mental health in a dose-response manner (e.g., articles read: Q2 aOR 1.31 (95% CI 1.01-1.70), Q3 aOR 1.68 (95% CI 1.30-2.17), Q4 1.99 (95% CI 1.54-2.59)). Improvements in medical knowledge and high perceived support were both associated with better perceived mental health management. Results were similar in users with and without a mental health condition. Discussion: These results suggest that access to a diverse set of digital resources provides multiple pathways to managing depression and anxiety during pregnancy for those with and without a diagnosed mental health condition.